Independent Subsystems of Atomic Hydrogen in Silicon Responsible for Boron Passivation and for Dimer Production. Issue 17 (9th June 2022) - Voronkov, Vladimir V.
Abstract : Herein, the reported data on boron–hydrogen defects HB are analyzed to conclude that there are at least two independent hydrogen ions, H + (1) and H + (2), that passivate boron by forming the HB(1) and HB(2) defects, respectively. The two H + ( i )/HB( i ) subsystems differ remarkably by the value of the transport parameter DK (a product of the H + diffusivity and the equilibrium dissociation constant of HB). There are numerous pairing reactions involving different single‐hydrogen species in positive and neutral charge states, and producing various kinds of dimeric hydrogen H2 . Within this model, a good fit to plasma‐induced hydrogen profiles (including a complicated shape found in boron‐implanted sample) is obtained. Abstract : The reported data on boron–hydrogen defects HB are analyzed to conclude that there are at least two independent hydrogen ions, H + (1) and H + (2), that passivate boron by forming the HB(1) and HB(2) defects, respectively. There are numerous pairing reactions that produce various kinds of dimeric hydrogen H2. A good fit is obtained to plasma‐induced hydrogen profiles (attached later).